Anti-Quorum Sensing Activity of Stevia Extract, Stevioside, Rebaudioside A and Their Aglycon Steviol - Victor Markus; Orr Share; Kerem Teralı; Nazmi Ozer; Robert S. Marks; Ariel Kushmaro; Karina Golberg (Molecules, 2020)
Governments are creating regulations for consumers to reduce their sugar intake, prompting companies to increase the ratio of artificial sweeteners in their products. However, there is evidence of some deleterious effects ascribed to the aforementioned synthetic agents and therefore consumers and food manufacturers have turned their attention to natural dietary sweeteners, such as stevia, to meet their sweetening needs. Stevia is generally considered safe; however, emerging scientific evidence has implicated the agent in gut microbial imbalance. In general, regulation of microbial behavior is known to depend highly on signaling molecules via quorum sensing (QS) pathways. This is also true for the gut microbial community. We, therefore, evaluated the possible role of these stevia-based natural sweeteners on this bacterial communication pathway. The use of a commercial stevia herbal supplement resulted in an inhibitory effect on bacterial communication, with no observable bactericidal effect. Purified stevia extracts, including stevioside, rebaudioside A (Reb A), and steviol revealed a molecular interaction, and possible interruption of Gram-negative bacterial communication, via either the LasR or RhlR receptor. Our in-silico analyses suggest a competitive-type inhibitory role for steviol, while Reb A and stevioside are likely to inhibit LasR-mediated QS in a non-competitive manner. These results suggest the need for further safety studies on the agents.